Sintering of alumina in the presence of liquid phase - Kant Singh V.I. (My University, 2025)
Sintering of alumina has been carried out in presence of two eutectic glass compositions, viz. CAS (1): CaO-23.0, Al2O3-15.0, SiO2-62.0 and CAS (2): CaO-52.0, Al2Os- 41.5, Si02-6.5.10,15,20 and 25 per cent by weight glass were used with different particle sizes of A1203 and sintered at 1400° and 1460°C. Effect of particle size of A1203 and glass content were studied from isothermal density variation. It was found that CAS(2) glass was more effective in promoting sintering of A1203 than CAS (1). © 1978, Taylor & Francis Group, LLC.